The Role of Social Studies Teachers in Reinforcing Social Values to Prevent Student Fights - Harianda, Jaka Rizkiawan; Asiyah; Gilang, M. Ilham (Entita: Jurnal Pendidikan Ilmu Pengetahuan Sosial dan Ilmu-Ilmu Sosial, 2026)
Education is the cornerstone of developing human resources who are not onlyacademically excellent but also possess good character and social behaviour.Instilling these values is crucial in preventing conflicts, particularly fights betweenpupils within the school environment. Therefore, the role of teachers, particularlySocial Studies teachers, is highly strategic in shaping and reinforcing social valuesamong pupils. This study aims to: (1) describe the role of Social Studies teachers inreinforcing social values in Year 9 at SMPN 06 Seluma, and (2) describe the socialvalues instilled by Social Studies teachers to prevent conflicts and fights amongstudents. The research method employed was a qualitative approach, with datacollection techniques including interviews, observation, and documentation. Researchfindings indicate that the role of social studies teachers in reinforcing social values iscrucial in shaping pupils’ social behaviour and preventing conflicts and fights. Thisrole is manifested through five key functions: as educators, mentors, motivators,evaluators, and facilitators. Teachers do not merely deliver lesson content, but alsoinstil values through setting a good example, fostering habits, providing guidance,offering motivation, and monitoring pupils’ behaviour.